(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this article, we looked at the short- and long-term effects of the global social mediamovement MeToo. With self-report questionnaires among US participants recruited online, we followedchanges in dismissal of sexual assault through four waves of measurement twice before the MeToomovement, at the peak of the MeToo, and six months later. Individual differences in gender, genderand feminist identification, and social dominance orientation were used to determine who will be mostor least affected by the movement (SDO). Following MeToo, both men and women were less likely toreject sexual assault, and this trend continued six months later. SDO reduced this effect, with low-SDOmen and high-SDO women having the greatest drop in dismissal of sexual assault. We found noevidence of a backlash impact, as previous article and vociferous critics of MeToo claimed. A possibleexplanation for SDO’s unique influence is examined, as well as the implications for social changeattempts.The restricting effects of legislation and legal language on public debate of sexual assault arehighlighted by MeToo and other forms of consciousness-raising for sexual violence. We discoveredthat, ironically, in the instance of sexual violence, the law has the potential to undercut the goals andbenefits of awareness-raising initiatives by private the experience of sexual assault and silencing itsvictims.